Respuesta de líneas promisorias de arroz (oriza sativa l.) a diferentes niveles de nitrógeno y épocas de aplicación en condiciones de riego y trasplante - Torres Moyano, Luis Rodrigo (2012)
This research was conducted in the South Coast Station "Dr. Enrique Ampuero Pareja", located at Km 26 via Duran Tambo, Canton Yaguachi, Parroquia “Virgen de Fátima” which is located 17 m, 2 ° 15 'south latitude and 79 º 54' west longitude, with annual temperature of 26 º C, average annual rainfall of 1025 mm, and 83% relative humidity, annual average. This experiment aimed to: 1) Determine the best time of nitrogen application in two promising lines, 2) Identify the appropriate dose of nitrogen to obtain high grain yield and 3) Conduct an economic analysis of the treatments under study based on CIMMYT. The experiment consisted of 3 cultivars, which were IN-15, GO-39590 and GO-38426, three doses of nitrogen, 60 - 120 and 180 kg N / ha, two times of application, 10-30 and 10-30 - 50 days after transplantation and 3 witnesses without nitrogen, with a total of 21 treatments. All these treatments were analyzed by a design of completely randomized blocks in a group.......